Working customers against online hate speech: Driven by high perceptions of personal abilities and benefits - Löschke, Ayaka (International Workshop “East Asia in the Digital Age: Digital Transformation in Technological, Economic and Social Perspective, 2022)
Social media platforms are available free of charge in exchange for users’ free labor such as watching advertisements. While such labor has increased recently, some social media users even started to report systematically online hate speech to internet service providers in democratic countries. What, for example, drove Twitter users to carry out and maintain their engagement? Using a theoretical framework offered by a German case study, this research conducts a Japanese case study and shows results of inductive qualitative analysis of classifying 1,038 participants in the #Internet Rightists Ban Festival launched in 2018 and their 3,821 tweets. It is argued that the Japanese user engagement has been driven especially by the perception of personal abilities, such as gaming and comment-writing skills, and the perception of personal benefits, especially from gamification and irony.<br